Resistance to regulatory T cell-mediated suppression in rheumatoid arthritis can be bypassed by ectopic foxp3 expression in pathogenic synovial T cells. - Beavis, P; Gregory, B; Green, P; Cribbs, A; Kennedy, A; Amjadi, P; Palfreeman, A; Feldmann, M; Brennan, F (2011)
Increasing evidence suggests that regulatory T cell (Treg) function is impaired in chronic inflammatory diseases such as rheumatoid arthritis (RA). Here we demonstrate that Tregs are unable to modulate the spontaneous production of TNF-α from RA synovial cells cultured from the diseased synovium site. Cytokine (IL-2, IL-6, TNF-α) activated T cells (Tck), cells we previously demonstrated to mimic the effector function of pathogenic RA synovial T cells, contained Tregs that survived and divided in this cytokine environment; however, the up-regulation of key molecules associated with Treg function (CTLA-4 and LFA-1) was impaired. Furthermore, Tregs were unable to suppress the function of Tcks, including contact-dependent induction of TNF-α from macrophages, supporting the concept that impaired Treg function/responsiveness contributes to chronicity of RA. However, ectopic foxp3 expression in both Tcks and pathogenic RA synovial T cells attenuated their cytokine production and function, including contact-dependent activation of macrophages. This diminished response to cytokine activation after ectopic foxp3 expression involved inhibited NF-κB activity and differed mechanistically from that displayed endogenously in conventional Tregs. These results suggest that diseases such as RA may perpetuate owing to the inability of Tregs to control cytokine-activated T-cell function. Understanding the mechanism whereby foxp3 attenuates the pathogenic function of synovial T cells may provide insight into the mechanisms of chronicity in inflammatory disease and potentially reveal new therapeutic candidates.